Two narratives about Poland and society. Analysis of news programmes: Fakty TV and Wiadomości TVP - Kotras, Marcin; Urbańska, Maja (Władza Sądzenia, 2023)
The media landscape in Poland is increasingly polarised, with broadcasters promoting biased narratives that conveniently omit certain issues that do not align with their agenda. These narratives use rhetorical devices and symbolism to manipulate people’s perception of social reality and cultivate a shared worldview that legitimises their stance. This polarisation is linked to political parallelism, where media outlets align themselves with specific political factions and abandon their impartiality.In Poland, identity media is prevalent, with broadcasters providing pre-packaged interpretations of news stories that further fuel the polarisation. It creates echo chambers, also known as epistemic bubbles.The study examined news coverage from Wiadomości TVP and Fakty TVN, analysing the narratives presented and the values and topics covered. Broadcasters promoted different narratives, contributing to social divisions and strengthening dichotomy, with fixed topics dominating the coverage. The study underscores the media’s significant role in changing public opinion pressure, especially in controlling the authorities.